Inflammatory Cytokines and BDNF Response to High-Intensity Intermittent Exercise: Effect the Exercise Volume - Cabral-Santos, Carolina; Castrillón, Carlos I. M.; Miranda, Rodolfo A. T.; Monteiro, Paula A.; Inoue, Daniela S.; Campos, Eduardo Z.; Hofmann, Peter; Lira, Fábio S. (Frontiers in Physiology, 2016)
The purpose of this study was to compare the effects of two similar high-intensity intermittent exercises (HIIE) but different volume 1.25 km (HIIE1.25) and 2.5 km (HIIE2.5) on inflammatory and BDNF responses. Ten physically active male subjects (age 25.22 ± 1.74 years, body mass 78.98 ± 7.31 kg, height 1.78 ± 0.06 m, VO2peak 59.94 ± 9.38 ml·kg·min−1) performed an incremental treadmill exercise test and randomly completed two sessions of HIIE on a treadmill (1:1 min at vVO2max with passive recovery). Blood samples were collected at rest, immediately and 60-min after the exercise sessions. Serum was analyzed for glucose, lactate, IL-6, IL-10, and BDNF levels. Blood lactate concentrations was higher immediately post-exercise compared to rest (HIIE1.25: 1.69 ± 0.26–7.78 ± 2.09 mmol·L−1, and HIIE2.5: 1.89 ± 0.26–7.38 ± 2.57 mmol·L−1, p < 0.0001). Glucose concentrations did not present changes under the different conditions, however, levels were higher 60-min post-exercise than at rest only in the HIIE1.25 condition (rest: 76.80 ± 11.14–97.84 ± 24.87 mg·dL−1, p < 0.05). BDNF level increased immediately after exercise in both protocols (HIIE1.25: 9.71 ± 306–17.86 ± 8.59 ng.mL−1, and HIIE2.5: 11.83 ± 5.82–22.84 ± 10.30 ng.mL−1). Although both exercises increased IL-6, level percent between rest and immediately after exercise was higher in the HIIE2.5 than HIIE1.25 (30 and 10%; p = 0.014, respectively). Moreover, IL-10 levels percent increase between immediately and 60-min post-exercise was higher in HIIE2.5 than HIIE1.25 (37 and 10%; p = 0.012, respectively). In conclusion, both HIIE protocols with the same intensity were effective to increase BDNF and IL-6 levels immediately after exercise while only IL-10 response was related to the durantion of exercise indicanting the importance of this exercise prescription variable.